Pengaruh Durasi Sonic Bloom Terhadap Perkembangan Penyakit Antraknosa Pada Tanaman Cabai Rawit (Capsicum frustescens) - Raudhatul Jannah; Yusriadi Marsuni; Salamiah Salamiah (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Anthracnose disease is caused by the pathogen Colletotrichum spp. which attacks cayenne pepper plants. This disease can reduce the quantity and quality of cayenne pepper fruit, causing losses. One of the existing sound technologies is Sonic Bloom. Sonic bloom is a sound wave technology with a certain frequency to determine the development of plant growth. There is very little research on plant diseases. This study aims to determine whether sonic bloom has an effect on anthracnose disease caused by Colletotrichum spp. The method used was Completely Randomized Design (CRD) consisting of 4 treatments, each treatment consisting of 6 replications so that 24 experimental units were obtained with 1 plant in each experiment carried out in-vivo. Observations were made by measuring disease incidence, plant height, number of fruit and fruit weight. The results obtained in this study showed that the sonic bloom treatment was able to reduce the percentage of anthracnose disease caused by the fungus Colletotrichum spp. on cayenne pepper plants. Sonic bloom has not been able to affect the height of cayenne pepper plants and inhibit the incubation period, but sonic bloom has been able to increase the weight of cayenne pepper fruit.